2015
DOI: 10.4314/ajtcam.v12i6.12
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of wound healing and antibacterial properties of methanolic root extract of <i>Stephania dinklagei</i> (Engl.) Diels

Abstract: Background: Stephania dinklagei Diels (Engl.) is used in folkloric medicine in Southeastern Nigeria for the treatment of wounds and some bacterial-associated infections. This study evaluated the wound healing and antibacterial potential of Stephania dinklagei to validate or invalidate its folkloric use. Materials and Methods:The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of methanolic extract of S. dinklagei root (MESDR) against Pseudomonas aeruginosa, Bacillus subtilis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…It is important that selected plant is identified by an expert/plant taxonomist and deposited in a reliable herbarium for future identification and reproducibility of study [ 27 ]. While most of the studies on antimicrobial activity of Nigerian medicinal plants reported expert identification of selected plant(s), only few papers [ 49 - 60 ] reported deposition of plant in herbarium with the accompanying voucher number. Selection of the plant part to be evaluated may be based on ethnomedical use, randomly or follow-up of antimicrobial activity [ 61 ].…”
Section: Experimental Approach Used In Antimicrobial Investigation Ofmentioning
confidence: 99%
See 4 more Smart Citations
“…It is important that selected plant is identified by an expert/plant taxonomist and deposited in a reliable herbarium for future identification and reproducibility of study [ 27 ]. While most of the studies on antimicrobial activity of Nigerian medicinal plants reported expert identification of selected plant(s), only few papers [ 49 - 60 ] reported deposition of plant in herbarium with the accompanying voucher number. Selection of the plant part to be evaluated may be based on ethnomedical use, randomly or follow-up of antimicrobial activity [ 61 ].…”
Section: Experimental Approach Used In Antimicrobial Investigation Ofmentioning
confidence: 99%
“…The storage conditions of plant material (whole/extract) have been shown to affect the result of antimicrobial studies by impacting microbial efficacy [ 16 , 64 , 73 ]. Some papers on Nigerian plants reported storage of extract in refrigerator at 4°C [ 18 , 59 , 60 , 74 ]. This storage condition is good because the activity/growth of possible extract-contaminating organisms would be inhibited and this in a way enhances the reliability of the result [ 16 , 75 ].…”
Section: Experimental Approach Used In Antimicrobial Investigation Ofmentioning
confidence: 99%
See 3 more Smart Citations